The Influence of Brand Preference, Perceived Quality, and Brand Trust on Repurchase Intention (A Study on Somethinc Product Users in Surabaya) - Sekar Harum Puspita; R. Yuniardi Rusdianto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The phenomenon of increasing consumer interest in local skincare products, along with the importance of understanding the variables influencing repurchase intention, has become increasingly relevant. Therefore, this study aims to examine the effect of brand preference, perceived quality, and brand trust on repurchase intention among users of Somethinc products in Surabaya. This research employed a quantitative approach, with data collected through questionnaires distributed to 150 respondents. The questionnaire was developed using a likert scale, and the data were analyzed through multiple linear regression. The results of the study reveal that: (1) Brand preference, perceived quality, and brand trust together have a significant influence on the repurchase intention of Somethinc products in Surabaya; (2) Brand preference has a positive and significant partial influence on repurchase intention; (3) Perceived quality has a positive and significant partial influence on repurchase intention; and (4) Brand trust has a positive and significant partial influence on the repurchase intention of Somethinc products in Surabaya.